Damage Localization and Quantification of Beams Using Wavelet Transform - Amir Ezzodin; Hosein Naderpour; Ali Kheyroddin; Gholamreza Ghodrati Amiri (مجله مدل سازی در مهندسی, 2015)
In recent years, damage detection and structural health monitoring methods for civil and mechanical structures, have been developed in different fields. Structural health monitoring is the implementation of a damage identification strategy to the civil engineering infrastructures. Damage is defined as changes to the material and/or geometric properties of these systems, including changes to the boundary conditions and system connectivity. Damage affects the current or future performance of such systems. Structural health monitoring and damage detection has several techniques, the methods are categorized based on the type of measured data used, and/or the technique used to identify the damage from the measured data. Wavelet transform is relatively new mathematical tool for signal processing. Wavelet transform gives more information on non-stationary signal that the Fourier transform was unable to provide them. One of the most important issue of application of the mathematical transforms such as wavelet, is structural health monitoring and structural damage detection. Especially the identification of damage in structures at the beginning is important. In this paper a simple method based on Wavelet transform has been utilized in order to localize and quantify the crack in simple supported beam in which, the deflection of the beam subject to static loading would be decomposed by discrete wavelet transforms. In decomposition diagrams has been assessed for various scenarios of damage. Finally the performance of the applied method has been evaluated for different state of cracking